MicroRNA-340-5p suppressed rheumatoid arthritis synovial fibroblast proliferation and induces apoptotic cell number by targeting signal transducers and activators of transcription 3 - Shibin Zhang; Tingting Meng; Chunzhi Tang; Shengdong Li; Xudong Cai; Dawei Wang; Min Chen (Taylor & Francis Group, 2020)
Rheumatoid arthritis is a chronic systemic autoimmune disease. In this study, the role of microRNA-340-5p in rheumatoid arthritis was investigated. qRT-PCR was used to detect the expression of microRNA-340-5p in serums, synovial tissues, and fibroblast-like synoviocytes from patients and healthy participants. Cell proliferation rate, cell cycle and apoptotic cell numbers were measured by CCK-8 and flow cytometry assays. The expression of pro-inflammation factors was determined by ELISA. Our data showed that the expression of microRNA-340-5p was greatly suppressed in rheumatoid arthritis serums, synovial tissues and rheumatoid arthritis-fibroblast-like synoviocytes compared to that in healthy controls. Over-expression of microRNA-340-5p greatly suppressed cell proliferation, promoted cell apoptosis, and suppressed the expression of inflammation factors in rheumatoid arthritis fibroblast-like synoviocytes. Additionally, STAT3 was a target of microRNA-340-5. Overexpression of STAT3 could reverse the outcome of microRNA-340-5p on cell proliferation and apoptosis in rheumatoid arthritis fibroblast-like synoviocytes. The findings in our study demonstrated that microRNA-340-5p may serve as a potential target for therapeutic direction for patients with rheumatoid arthritis.